The lost papers : managing an academic institution (A) - Barua, S. K. (Samir K.) (London : SAGE Publications Ltd, 2017)
The case illustrates situations that often arise in an organization that have ethical dilemmas for various functionaries in the organization. The perspective of the functionaries is coloured by the role they play in the organization and their perception of their responsibility and accountability. Should pragmatism in such tricky situations over-ride the need for ensuring natural justice to those who may be negatively impacted by the situation? Should ethics and integrity over-ride the risk of loss of reputation an organization may run, at least in the short term, for being ethical? What should the individuals do if they have to deal with authority that may ask them to be unethical? The case provides an interesting context to discuss such imponderable issues.
Originally published: Barua, S. (2013). The Lost papers: Managing an academic institution (A). RJMC0027. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; College personnel management -- Case studies; Universities and colleges -- Moral and ethical aspects -- Case studies